Profitable paddy-paddy enterprise of tenant farmer in Eluru District of Andhra Pradesh - Srinivas, T; Suneetha, Y; Jamedar, Harsha Vardhan Rayudu (Indian Farming, 2024)
The article describes the inspiring story of Bandi Trimurthulu, a tenant farmer from Unguturu Mandal, Bommidi Village in Eluru district of Andhra Pradesh who successfully overcame the challenges and earned an income of 1.21 lakhs from agriculture. Trimurthulu's journey offers hope to unemployed youth and others, particularly those engaged in paddy farming.